THE NATURE AND AMBIT OF THE INTIMIDATION OFFENCE S v White 2022 (2) SACR 511 (FB) - Shannon Hoctor (Obiter, 2023)
The offence of intimidation has been associated with controversy, particularly because of the historical link between the Intimidation Act (72 of 1982) and the legislative machinations of the apartheid regime. In the words of Gamble J, the Act may be regarded as “a piece of apartheid order legislation introduced at a time of increasingly repressive internal security legislation designed to criminalise conduct, largely in the field of resistance politics” (Sandlana v Minister of Police 2023 (2) SACR 84 (WCC) par 34). The nature and ambit of the intimidation offence has once again come under scrutiny in the recent case of S v White (2022 (2) SACR 511 (FB)). The decision in this case is examined here in the context of a general assessment of the offence. The offence can now only be committed by contravening section 1(1)(a) of the Act, as the Constitutional Court has struck down the section 1(1)(b) provision (as well as section 1(2)) as unconstitutional in Moyo v Minister of Police (2020 (1) SACR 373 (CC)), a development confirmed by the amendment of the Act by the Protection of Constitutional Democracy Against Terrorist and Related Activities Amendment Act (23 of 2022). (Some are of the view that the Constitutional Court could have gone further (Burchell Principles of Criminal Law 5ed (2016) 593–594).) However, for the purposes of the discussion that follows, it is useful to cite the full section 1(1) provision prior to amendment.